2020
DOI: 10.2196/13761
|View full text |Cite
|
Sign up to set email alerts
|

Adoption of an Electronic Patient Record Sharing Pilot Project: Cross-Sectional Survey

Abstract: Background The Public Private Interface–Electronic Patient Record (PPI-ePR) system was implemented as a new electronic platform to facilitate collaboration between the public and private sectors in Hong Kong. However, its barriers to participate and benefits have not been comprehensively assessed. Objective This study aimed to evaluate the awareness, acceptance, perceived benefits, and obstacles to participation among private doctors and the general pub… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 38 publications
3
10
0
Order By: Relevance
“…Many of the studies [ 47 , 68 , 77 , 80 , 82 , 100 , 101 , 109 - 112 , 114 ] have explored patient experiences with access to patient portals and subsequently access to their own medical information. All of the studies reported that users were highly satisfied with the access, and in one study, 97% of survey respondents stated that they would definitely or probably recommend the portal to other clients and families [ 110 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Many of the studies [ 47 , 68 , 77 , 80 , 82 , 100 , 101 , 109 - 112 , 114 ] have explored patient experiences with access to patient portals and subsequently access to their own medical information. All of the studies reported that users were highly satisfied with the access, and in one study, 97% of survey respondents stated that they would definitely or probably recommend the portal to other clients and families [ 110 ].…”
Section: Resultsmentioning
confidence: 99%
“…In total, 18 studies [ 40 - 42 , 50 , 51 , 54 , 55 , 57 , 64 , 66 , 82 , 87 , 120 - 125 ] and 3 reports [ 114 , 126 , 127 ] addressed the health care workforce perspective through various methods (mixed methods, n=7; prospective observational, n=2; qualitative, n=6; and surveys, n=6), with a focus on conducting formative and process evaluations. A total of 11 studies were conducted in the United States, 5 in Sweden, 4 in Canada, and 1 in China.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many of the studies [47,68,77,80,82,100,101,[109][110][111][112]114] have explored patient experiences with access to patient portals and subsequently access to their own medical information. All of the studies reported that users were highly satisfied with the access, and in one study, 97% of survey respondents stated that they would definitely or probably recommend the portal to other clients and families [110].…”
Section: Benefits Of Accessmentioning
confidence: 99%
“…In total, 18 studies [40][41][42]50,51,54,55,57,64,66,82,87,[120][121][122][123][124][125] and 3 reports [114,126,127] addressed the health care workforce perspective through various methods (mixed methods, n=7; prospective observational, n=2; qualitative, n=6; and surveys, n=6), with a focus on conducting formative and process evaluations. A total of 11 studies were conducted in the United States, 5 in Sweden, 4 in Canada, and 1 in China.…”
Section: Health Care Workforcementioning
confidence: 99%